A multi-layer composite structure coating tool and preparation method thereof

By depositing multi-layer composite structural coatings on the tool, including CrN, CrAlN, (ZruCrv)B2 and (ZrxYy)B2, the problem of difficulty in meeting the performance requirements of the tool under extreme conditions is solved by the existing technology, and higher wear resistance, oxidation resistance and mechanical strength are achieved, and the service life of the tool is extended.

CN119465030BActive Publication Date: 2025-04-11GANZHOU ACHTECK TOOL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510053954.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to meet the performance requirements of tool wear resistance, adhesion resistance and thermal crack resistance under extreme conditions when processing difficult materials such as titanium alloys, nickel-based alloys and iron-based alloys.

Method used

These layers are deposited by physical vapor deposition using a multi-layer composite structural coating tool, including a substrate and sequentially deposited CrN coating, CrAlN coating, (ZruCrv)B2 and (ZrxYy)B2 gradient alternating coating, and (ZrxYy)B2 coating.

Benefits of technology

It significantly improves the oxidation resistance, wear resistance and mechanical strength of the coating, meets the processing needs in extreme environments in the fields of aerospace, military industry, chemical industry, etc., and extends the service life of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465030B_ABST
    Figure CN119465030B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of coated tool technology, and provides a multi-layer composite structure coated tool and a preparation method thereof, comprising a substrate and a multi-layer composite structure coating sequentially deposited on the surface of the substrate by a physical vapor deposition method, wherein the multi-layer composite structure coating comprises a CrN coating, a CrAlN coating, (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating, (Zr x Y y )B2 coating. The present invention significantly improves the oxidation resistance, wear resistance and mechanical strength of the coating through a multi-layer structure design to meet the processing and use requirements in extreme environments in the fields of aerospace, military industry, chemical industry, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coated tool technology, and specifically relates to a multi-layer composite structure coated tool and a preparation method thereof. Background Art

[0002] With the rapid development of industries such as aerospace, energy, and chemical industry, the demand for difficult-to-process materials such as titanium alloys, nickel-based alloys, and iron-based alloys is increasing. Titanium alloys have high strength ratios, excellent corrosion resistance, and biocompatibility, but their wear resistance is relatively poor. During processing, the tool is easily worn, affecting processing efficiency and workpiece quality. Nickel-based alloys have excellent properties such as high temperature strength, corrosion resistance, and resistance to cold and hot fatigue, and have high hardness and difficult processing. Iron-based alloys are one of the commonly used materials in the machinery manufacturing industry, and their processing performance is affected by many factors such as material composition, organizational structure, and heat treatment process. When processing iron-based alloys, the tool needs to have good wear resistance, anti-adhesion, and thermal crack resistance. Based on the above situation, higher requirements are placed on tool coatings during processing, so the development of tool coatings with high performance, long life, and low cost has become an urgent market demand.

[0003] As an existing surface treatment technology, PVD technology has been widely used in the development of cemented carbide tool coatings. PVD coatings have the advantages of high hardness, high wear resistance, high adhesion and good corrosion resistance, and can meet the processing requirements of difficult-to-process materials such as titanium alloys, nickel-based alloys, and iron-based alloys. CrN coatings are widely used in many fields due to their excellent hardness, wear resistance and corrosion resistance. However, a single coating is difficult to meet all performance requirements under certain extreme conditions. Therefore, the development of multi-layer composite coatings has become an important direction to improve material performance. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a multi-layer composite structure coating tool and a preparation method thereof.

[0005] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0006] A multi-layer composite structure coating tool comprises a substrate and a multi-layer composite structure coating sequentially deposited on the surface of the substrate by a physical vapor deposition method, wherein the multi-layer composite structure coating comprises a CrN coating, a CrAlN coating, (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating, (Zr x Y y )B2 coating, where 4u+3v=4, 4x+3y=4.

[0007] As a preferred solution of the multi-layer composite structure coating tool described in the present invention, the total thickness of the multi-layer composite structure coating is 2.6-4.4 μm.

[0008] As a preferred embodiment of the multi-layer composite structure coating tool of the present invention, wherein: the (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating thickness is gradient alternating, with a total thickness of 0.8~1.2μm, among which (Zr u Cr v )B2 coating thickness gradient decreases from 30nm to 10nm, with 40~60 layers. (Zr x Y y ) The thickness gradient of B2 coating increases from 10nm to 30nm, and the number of layers is 40~60.

[0009] As a preferred embodiment of the multi-layer composite structure coating tool of the present invention, wherein: the (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr u Cr v )B2 alternating layer is (Zr u Cr v )B2 solid solution phase, (Zr x Y y )B2 alternating layer is (Zr x Y y )B2 solid solution phase, (Zr u Cr v )B2 alternating layer, (Zr x Y y )B2 alternating layers are all hexagonal crystal structures, and the fracture morphology of the coating is mainly in the form of columnar crystal growth. u Cr v The grain size of the B2 alternating layer ranges from 0.4 to 0.8 μm. x Y y )The grain size of the B2 alternating layer ranges from 0.5 to 1.0 μm.

[0010] As a preferred embodiment of the multi-layer composite structure coated tool described in the present invention, the CrN coating structure is a cubic crystal structure, the fracture morphology of the CrN coating is mainly in the form of equiaxed crystal growth, the grain size of the CrN coating ranges from 20 to 40 nm, and the thickness of the CrN coating is 0.3 to 0.7 μm.

[0011] As a preferred embodiment of a multi-layer composite structure coated tool described in the present invention, the CrAlN coating is a CrAlN solid solution phase, the structure is a cubic crystal structure, the fracture morphology of the CrAlN coating is mainly in the form of equiaxed crystal growth, the grain size range of the CrAlN coating is 15~20nm, the thickness of the CrAlN coating is 1.2~1.8μm, and the atomic ratio of Cr to Al is 0.33~1.

[0012] As a preferred embodiment of the multi-layer composite structure coating tool described in the present invention, wherein: (Zr x Y y )B2 coating is (Zr x Y y )B2 solid solution phase, (Zr x Y y )B2 coating has a hexagonal crystal structure, and the fracture morphology of the coating is mainly in the form of columnar crystal growth. x Y y The grain size of the B2 coating ranges from 0.5 to 1.0 μm. x Y y )B2 coating thickness is 0.3~0.7μm.

[0013] As a preferred solution of the multi-layer composite structure coating tool described in the present invention, the substrate is made of any one of cemented carbide, high-speed steel, metal ceramic, polycrystalline diamond, cubic boron nitride and other materials.

[0014] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:

[0015] A method for preparing the above-mentioned multi-layer composite structure coating tool, depositing the multi-layer composite structure coating on the substrate by physical vapor deposition method;

[0016] The (Zr u Cr v )B2 and (Zr x Y y ) The deposition parameters of B2 gradient alternating coating are:

[0017] (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr u Cr v )B2 alternating layer at a temperature of 730~770℃, an Ar pressure of 4~6Pa, and a bias voltage of 50~60V on the substrate, (Zr u Cr v)B2 target material is deposited under the condition of power supply of 2000~4500W, (Zr u Cr v )B2 target power source is deposited in sequence with different (Zr u Cr v )B2 alternating layer with gradient change from 4500W to 2000W;

[0018] (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr x Y y )B2 alternating layer at a temperature of 730~770℃, an Ar pressure of 4~6Pa, and a bias voltage of 50~60V on the substrate, (Zr x Y y )B2 target material is deposited under the condition of power supply of 2000~4500W, (Zr x Y y )B2 target power source is deposited in sequence with different (Zr x Y y )B2 alternating layer with a gradient change from 2000W to 4500W.

[0019] As a preferred embodiment of the method for preparing the multi-layer composite structure coated tool described in the present invention, the CrN coating is deposited under the conditions of a temperature of 730-770°C, a N2 pressure of 6-8Pa, a target power supply of 8000-12000W, and a bias voltage of 70-80V on the substrate.

[0020] As a preferred embodiment of the method for preparing the multi-layer composite structure coated tool of the present invention, wherein:

[0021] The CrAlN coating is deposited at a temperature of 730~770℃, a N2 pressure of 6~8Pa, a target power supply of 8000~12000W, and a bias voltage of 60~70V on the substrate.

[0022] As a preferred embodiment of the method for preparing a multi-layer composite structure coating tool according to the present invention, wherein: (Zr x Y y ) The B2 coating was deposited at a temperature of 730~770℃, an Ar pressure of 4~6Pa, a target power supply of 2000~4500W, and a bias voltage of 40~50V on the substrate.

[0023] The beneficial effects of the present invention are as follows:

[0024] The present invention provides a multi-layer composite structure coating tool and a preparation method thereof, comprising a substrate and a multi-layer composite structure coating sequentially deposited on the surface of the substrate by a physical vapor deposition method, wherein the multi-layer composite structure coating comprises a CrN coating, a CrAlN coating, (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating, (Zr x Y y )B2 coating. The present invention significantly improves the oxidation resistance, wear resistance and mechanical strength of the coating through a multi-layer structure design to meet the processing and use requirements in extreme environments in the fields of aerospace, military industry, chemical industry, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0026] Figure 1 It is a schematic cross-sectional view of a multi-layer composite structure coating tool of the present invention.

[0027] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0028] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] like Figure 1 The present invention provides a multi-layer composite structure coating tool and a preparation method thereof. The multi-layer composite structure coating tool comprises a substrate and a multi-layer composite structure coating sequentially deposited on the surface of the substrate by a physical vapor deposition method. The multi-layer composite structure coating comprises a CrN coating, a CrAlN coating, (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating, (Zr x Y y )B2 coating, where 4u+3v=4, 4x+3y=4.

[0030] The method for preparing the multi-layer composite structure coating tool comprises the following steps:

[0031] Step S1, substrate preparation: the substrate to be coated is pre-treated by cleaning, degreasing, and rust removal to ensure that the substrate surface is clean and free of impurities.

[0032] Step S2, CrN coating deposition: placing the pretreated substrate in a PVD coating furnace, and depositing a CrN coating on the surface of the substrate by ion bombardment or magnetron sputtering; the CrN coating as a base layer can enhance the bonding strength between the coating and the substrate;

[0033] Step S3, CrAlN coating deposition: on the CrN coating, continue to deposit the CrAlN coating; the CrAlN coating as a functional layer can enhance the oxidation resistance and corrosion resistance of the coating, and at the same time has a good bonding state with the base layer;

[0034] Step S4, (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating deposition: on top of the CrAlN coating, (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating; (Zr u Cr v )B2 and (Zr x Y y ) The B2 gradient alternating coating as a functional layer can improve the wear resistance and corrosion resistance of the coating, and also has a good bonding state with the CrAlN layer;

[0035] Step S5, (Zr x Y y )B2 coating deposition: in (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating is deposited on (Zr x Y y )B2 coating; (Zr x Y y ) B2 as the outermost layer can further improve the wear resistance and oxidation resistance of the coating. The good bonding between the above layers can greatly reduce the coating peeling caused by internal stress problems.

[0036] Step S6, post-processing: After the coating deposition is completed, post-processing such as sandblasting and polishing is performed to eliminate the stress inside the coating, thereby improving the bonding strength and stability of the coating.

[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0038] Example 1

[0039] A method for preparing a multi-layer composite structure coated tool, wherein the substrate is a WNMG 080408E-SC3 type hard alloy, comprises the following steps:

[0040] Step S1, substrate preparation: the substrate to be coated is pre-treated by cleaning, degreasing, and rust removal to ensure that the substrate surface is clean and free of impurities.

[0041] Step S2, CrN coating deposition: placing the pretreated substrate in a PVD coating furnace, and depositing a CrN coating on the surface of the substrate by ion bombardment or magnetron sputtering. The CrN coating is deposited at a temperature of 750°C, a N2 pressure of 7Pa, a target power supply of 10000W, and a bias voltage of 75V on the substrate, and has a thickness of 0.5 μm;

[0042] Step S3, CrAlN coating deposition: on the CrN coating, continue to deposit a CrAlN coating; obtain a CrAlN coating with excellent oxidation resistance and corrosion resistance, the CrAlN coating is deposited under the conditions of a temperature of 750°C, a N2 pressure of 7Pa, a target power supply of 10000W, and a bias voltage of 65V on the substrate, with a thickness of 1.5μm, wherein the atomic ratio of Cr to Al is 3:7;

[0043] Step S4, (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating deposition: on top of the CrAlN coating, (Zr u Cr v )B2 and (Zr x Y y ) B2 gradient alternating coating, total thickness is 1.0 μm;

[0044] (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr u Cr v )B2 alternating layers were deposited at 750℃, 5Pa Ar pressure, and 55V bias on the substrate. (Zr u Crv )B2 target power source is deposited in sequence with different (Zr u Cr v )B2 alternating layer with gradient change from 4500W to 2000W;

[0045] (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr x Y y )B2 alternating layers were deposited at 750℃, 5Pa Ar pressure, and 55V bias on the substrate. (Zr x Y y )B2 target power source is deposited in sequence with different (Zr x Y y )B2 alternating layer with gradient change from 2000W to 4500W;

[0046] Step S5, (Zr x Y y )B2 coating deposition: in (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating is deposited on (Zr x Y y )B2 coating, (Zr x Y y ) The B2 coating was deposited at a temperature of 750°C, an Ar pressure of 5 Pa, a target power supply of 3500 W, and a bias voltage of 45 V on the substrate, with a thickness of 0.5 μm;

[0047] Step S6: Post-processing

[0048] After the coating is deposited, post-treatment such as sandblasting and polishing is performed to eliminate the stress inside the coating, thereby improving the adhesion and stability of the coating.

[0049] Comparative Example 1

[0050] The difference from Example 1 is that steps S4-S5 are not performed, and a ZrB2 coating with a thickness of 1.5 μm is deposited on the CrAlN coating.

[0051] Comparative Example 2

[0052] The difference from Example 1 is that steps S4-S5 are not performed, and the thickness of the CrAlN coating in step S3 is 3 μm.

[0053] Example 2

[0054] The difference from Example 1 is that the substrate is APMT 1604PDER cemented carbide.

[0055] Comparative Example 3

[0056] The difference from Example 2 is that step S4 is ZrB2 and (Zr x Y y )B2 gradient alternating coating deposition: ZrB2 and (Zr x Y y )B2 gradient alternating coating, with a total thickness of 1.0μm.

[0057] Comparative Example 4

[0058] The difference from Example 2 is that step S4 is (Zr u Cr v )B2 and ZrB2 gradient alternating coating deposition: on top of the CrAlN coating, (Zr u Cr v )B2 and ZrB2 gradient alternating coatings, with a total thickness of 1.0 μm; step S5 is ZrB2 coating deposition: u Cr v )ZrB2 coating with a thickness of 0.5μm is deposited on the gradient alternating coating of B2 and ZrB2.

[0059] The performance of the cutting tools prepared in the embodiments and comparative examples was tested, and the results are shown in Table 1.

[0060] Table 1

[0061]

[0062] The following tests were conducted on the processing performance of the cutting tools prepared by the various embodiments and comparative examples of the present invention, wherein:

[0063] Test condition 1 is as follows:

[0064] Operation: Turning

[0065] Workpiece: cylindrical parts

[0066] Material: TC4

[0067] Cutting speed: 40m / min

[0068] Feed per tooth: 0.1mm / z

[0069] Cutting depth: 0.3mm

[0070] Wet cutting

[0071] The wear volume VB (unit: mm) measured results after cutting for 10 minutes, 20 minutes, 30 minutes, 40 minutes and 50 minutes are shown in the following Table 2 (- indicates failure).

[0072] Table 2

[0073]

[0074] It can be seen that under the same cutting conditions and cutting time, the wear amount of the tool prepared in Example 1 is significantly lower than that of Comparative Examples 1-2, indicating that the present invention greatly improves the service life of the tool.

[0075] Test condition 2 is as follows:

[0076] Operation: Face milling

[0077] Artifact: Block

[0078] Material: TC18

[0079] Cutting speed: 45 m / min

[0080] Feed per tooth: 0.6 mm / z

[0081] Cutting depth: 0.6 mm

[0082] Cutting width: 35 mm

[0083] Wet cutting

[0084] The wear volume VB (unit: mm) measurement results after cutting for 10 minutes, 30 minutes, 50 minutes, 0 minutes and 90 minutes are shown in the following Table 3 (- indicates failure).

[0085] Table 3

[0086]

[0087] It can be seen that under the same cutting conditions and cutting time, the wear amount of the tool prepared in Example 2 is significantly lower than that of Comparative Examples 3-4, indicating that the present invention greatly improves the service life of the tool.

[0088] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A multi-layer composite structure coating tool, characterized in that: The invention comprises a substrate and a multi-layer composite structure coating which is sequentially deposited on the surface of the substrate by a physical vapor deposition method, wherein the multi-layer composite structure coating comprises a CrN coating, a CrAlN coating, (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating, (Zr x Y y )B2 coating, where 4u+3v=4, 4x+3y=4.

2. The multi-layer composite structure coated tool according to claim 1, characterized in that: The total thickness of the multi-layer composite structure coating is 2.6~4.4μm.

3. The multi-layer composite structure coating tool according to claim 1, characterized in that: The (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating has a total thickness of 0.8~1.2μm; the (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr u Cr v )B2 coating thickness gradient decreases from 30nm to 10nm, with 40~60 layers. (Zr x Y y ) The thickness gradient of B2 coating increases from 10nm to 30nm, and the number of layers is 40~60.

4. The multi-layer composite structure coating tool according to claim 1, characterized in that: The (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr u Cr v )B2 alternating layer is (Zr u Cr v )B2 solid solution phase, (Zr x Y y )B2 alternating layer is (Zr x Y y )B2 solid solution phase, (Zr u Cr v )B2 alternating layer, (Zr x Y y )B2 alternating layers are all hexagonal crystal structures.

5. The multi-layer composite structure coating tool according to claim 1, characterized in that: The (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr u Cr v The grain size of the B2 alternating layer ranges from 0.4 to 0.8 μm. x Y y )The grain size of the B2 alternating layer ranges from 0.5 to 1.0 μm.

6. The multi-layer composite structure coating tool according to claim 1, characterized in that: The CrN coating has a cubic crystal structure, a grain size range of 20-40 nm, and a thickness of 0.3-0.7 μm.

7. The multi-layer composite structure coated tool according to claim 1, characterized in that: The CrAlN coating is a CrAlN solid solution phase, has a cubic crystal structure, has a grain size range of 15-20 nm, has a thickness of 1.2-1.8 μm, and has an atomic ratio of Cr to Al of 0.33-1.

8. The multi-layer composite structure coating tool according to claim 1, characterized in that: (Zr x Y y )B2 coating is (Zr x Y y )B2 solid solution phase, (Zr x Y y )B2 coating has a hexagonal crystal structure, (Zr x Y y The grain size of the B2 coating ranges from 0.5 to 1.0 μm. x Y y )B2 coating thickness is 0.3~0.7μm.

9. A method for preparing a multi-layer composite structure coated tool according to any one of claims 1 to 8, characterized in that: Depositing a multilayer composite structure coating on a substrate by a physical vapor deposition method; The (Zr u Cr v )B2 and (Zr x Y y ) The deposition parameters of B2 gradient alternating coating are: (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr u Cr v )B2 alternating layer at a temperature of 730~770℃, an Ar pressure of 4~6Pa, and a bias voltage of 50~60V on the substrate, (Zr u Cr v )B2 target material is deposited under the condition of power supply of 2000~4500W, (Zr u Cr v )B2 target power source is deposited in sequence with different (Zr u Cr v )B2 alternating layer with gradient change from 4500W to 2000W; (Zr u Cr v )B2 and (Zr x Y y )B2 gradient alternating coating (Zr x Y y )B2 alternating layer at a temperature of 730~770℃, an Ar pressure of 4~6Pa, and a bias voltage of 50~60V on the substrate, (Zr x Y y )B2 target material is deposited under the condition of power supply of 2000~4500W, (Zr x Y y )B2 target power source is deposited in sequence with different (Zr x Y y )B2 alternating layer with a gradient change from 2000W to 4500W.

Citation Information

Patent Citations

  • Multi-layer coating cutter and preparation method

    CN116162917A

  • Multilayered coated cutting tool

    US20110135898A1